2017
DOI: 10.1371/journal.ppat.1006138
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Insensitivity in Virally Infected Airway Epithelial Cells Is Dependent on Transforming Growth Factor-β Activity

Abstract: Asthma and chronic obstructive pulmonary disease (COPD) exacerbations are commonly associated with respiratory syncytial virus (RSV), rhinovirus (RV) and influenza A virus (IAV) infection. The ensuing airway inflammation is resistant to the anti-inflammatory actions of glucocorticoids (GCs). Viral infection elicits transforming growth factor-β (TGF-β) activity, a growth factor we have previously shown to impair GC action in human airway epithelial cells through the activation of activin-like kinase 5 (ALK5), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 73 publications
1
19
0
Order By: Relevance
“…Thus, partial abrogation of TGF-β 1 activity presents a clinically tractable approach to the treatment of fibrosis ( LaChapelle et al, 2018 ). Our efforts to identify the mechanism of TGF-β-induced glucocorticoid insensitivity ( Salem et al, 2012 ; Keenan et al, 2014 ; Xia et al, 2017 ) lead to a comprehensive literature review that revealed a little-known connection between TGF-β 1 signaling and casein kinase (CK) activity ( Hall et al, 1996 ). CK1ε physically interacts with Smad3 to mediate some TGF-β signals, including upregulation of the fibrogen, plasminogen-activator inhibitor-1 ( Waddell et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, partial abrogation of TGF-β 1 activity presents a clinically tractable approach to the treatment of fibrosis ( LaChapelle et al, 2018 ). Our efforts to identify the mechanism of TGF-β-induced glucocorticoid insensitivity ( Salem et al, 2012 ; Keenan et al, 2014 ; Xia et al, 2017 ) lead to a comprehensive literature review that revealed a little-known connection between TGF-β 1 signaling and casein kinase (CK) activity ( Hall et al, 1996 ). CK1ε physically interacts with Smad3 to mediate some TGF-β signals, including upregulation of the fibrogen, plasminogen-activator inhibitor-1 ( Waddell et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the global impact of TGF-β1 on GC gene regulation, we conducted RNA-seq analyses of extracts of BEAS-2B cells (n = 3) incubated with TGF-β1 (40 pM), and then exposed to dexamethasone (Dex, 30 nM), using concentrations previously established as maximally effective (Keenan et al., 2014, Salem et al., 2012, Xia et al., 2017). Genes influenced by TGF-β1 alone by more than 2-fold and those with smaller but significant changes (applying a Benjamini and Hochberg [BH] false discovery rate [FDR] < 0.05) were filtered from the analyzed set to avoid the confounding influence of direct TGF-β1 gene regulation.…”
Section: Resultsmentioning
confidence: 99%
“…However, the insensitivity induced by transforming growth factor β1 (TGF-β1) demands most attention because of its extraordinary capacity at picomolar concentrations to ablate GC anti-inflammatory activity in airway and lung epithelial cells (Keenan et al., 2014, Salem et al., 2012). Moreover, we have recently identified that viral infection of human bronchial epithelial cells impairs GC anti-inflammatory activity through the induction of TGF-β1 activity (Xia et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…TNF downregulates the levels of hepatic GR in vivo , whereas TGF-β exposure (before challenge with IL-1 α ) reduces GR levels in A549 cells ( 64 , 65 ). However, TGF-β induced by respiratory syncytial virus fails to downregulate GR levels in human airway epithelial cells ( 66 ). Proteasomal degradation of GR reduces its levels and was proposed to cause GC resistance in endothelial cells ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%